THE INFLUENCE OF EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE (A STUDY OF KOPI JANJI JIWA) - Genoveva; Fauziah, Nuffuz (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
This study aims to analyze whether experiential marketing affects consumer loyalty with customer satisfaction as a mediating variable in Janji Jiwa Coffee Shop. The research is based on a questionnaire data source that was distributed to consumers who made purchases during the Covid-19 pandemic. The number of samples used was 175 respondents. The method used is a quantitative method. The data obtained were analyzed using Partial Least Square (PLS) -SEM through SmartPLS 3.0 software. The sampling technique using purposive sampling is a sampling technique based on consideration of certain criteria and conditions and must represent the population to be studied. The results showed that the experiential marketing variable had a positive and significant effect on customer satisfaction. This is because several factors affect customer satisfaction, namely sense, feel, think, act, and relate. Consumer satisfaction has a positive and significant effect on consumer loyalty. And experiential marketing has a positive and significant influence on consumer loyalty mediated by customer satisfaction.